2019
DOI: 10.7759/cureus.4110
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Type 31-A1 Two-part Intertrochanteric Femur Fractures: Is Proximal Femoral Nail Superior to Dynamic Hip Screw Fixation?

Abstract: Introduction The implant of choice for two-part intertrochanteric femur fracture is still under debate. This study was done to compare the operative parameters and functional outcome of two-part intertrochanteric fractures treated by dynamic hip screw (DHS) and proximal femur nail (PFN). Methods Fifty-four operated cases of two-part intertrochanteric (AO 31A1) were analysed and divided into two groups based on implant used (PFN 30, DHS 24). Operative details, which include bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…II) This meta-analysis showed significantly shorter operative times, smaller incisions, and less intraoperative blood loss in PFN than in DHS. These were exactly our findings [23][24] . According to Zhang et al A higher (but not significant) infection rate was observed in the group of DHS.…”
Section: Resultssupporting
confidence: 91%
“…II) This meta-analysis showed significantly shorter operative times, smaller incisions, and less intraoperative blood loss in PFN than in DHS. These were exactly our findings [23][24] . According to Zhang et al A higher (but not significant) infection rate was observed in the group of DHS.…”
Section: Resultssupporting
confidence: 91%
“…After carefully reviewing entire manuscripts, 41 studies were excluded. Finally, 30 studies were included 11‐40 . The included studies were published between 2002 and 2022, with sample sizes ranging from 46 to 222 patients.…”
Section: Resultsmentioning
confidence: 99%
“…21,22 In stable ITFs, DHS and PFN have proven not to be superior to each other. 30 DHS was preferred in our study because compression in DHS was more pronounced than PFN and it was a cheaper implant for the treatment.…”
Section: Discussionmentioning
confidence: 99%